Neoadjuvant therapy and major arterial resection for potentially reconstructable arterial involvement by stage 3 adenocarcinoma of the pancreas. Issue 6 (June 2019) - Loveday, Benjamin P.T.; Zilbert, Nathan; Serrano, Pablo E.; Tomiyama, Koji; Tremblay, Amélie; Fox, Adrian M.; Segedi, Maja; O'Malley, Martin; Borgida, Ayelet; Bianco, Teresa; Creighton, Sean; Dodd, Anna; et al.
Abstract: Background: Stage 3 pancreatic ductal adenocarcinoma (PDAC) is defined by arterial involvement. This study objective was to evaluate outcomes for patients with stage 3 PDAC with potentially reconstructable arterial involvement, considered for neoadjuvant therapy (NAT) and pancreatic resection, and to compare outcomes following arterial (AR) and non-arterial resection (NAR). Methods: This study included patients from 2009 to 2016 with biopsy-proven stage 3 PDAC who were offered NAT before surgical exploration. AR was performed if required to achieve R0 resection. Time to event outcomes were analysed from diagnosis date. Results: 87/89 patients (97.8%) received NAT (chemotherapy 41.6%, chemotherapy/radiotherapy 56.2%). 46/89 (51.7%) underwent exploration; 31 underwent resection (AR n = 20, NAR n = 11). AR patients had longer operative time (681 vs. 563 min, p = 0.006) and more blood loss (1600 vs. 575 mL, p = 0.0004), with no difference for blood transfusion, pancreatic fistula, length of stay, reoperation, or mortality. R0 rate was 30/31. Post-resection 90-day mortality was 3.2%. Median overall survival was statistically comparable between the AR and NAR groups (19.7 vs. 28.4 months, p = 0.41). Conclusions: AR had comparable clinical and oncologic outcomes to NAR. Following careful selection and non-progression after NAT, major AR may cautiously be considered if required to obtain a negative resection margin.